Free transverse vibration of a wrinkled annular thin film by using finite difference method. (17th February 2016) - Wang, C.G.; Liu, Y.P.; Lan, L.; Tan, H.F.
Abstract: This paper investigates the free transverse vibration of a wrinkled annular thin film. The non-dimensional Hamilton motion equation of the wrinkled annular thin film is established, which is solved by using the finite difference method to acquire the vibration frequency and mode. The predicted vibration characteristics are verified by the experimental measurements based on the digital image correlation (DIC) technique. The results show that wrinkles have great effects on the vibration of the annular thin film. Especially for the heavily wrinkled cases, the local–global interactive mode dominates the vibration of the annular thin film. The frequency increases as the wrinkling level increases which is mainly due to the increased nonlinear geometric stiffness. The results provide favorable supports for understanding the role of nonlinear wrinkling on the vibration of thin films. Graphical abstract: Highlights: The Hamilton motion equation of wrinkled annular thin film is established. The vibration frequency and mode are solved by the finite difference method. The theoretical predictions are verified by the non-contacted DIC tests. The local–global interactive mode dominates the vibration of highly wrinkled thin film. The role of nonlinear wrinkling to the vibration of annular thin film is elucidated.